2017
DOI: 10.1093/toxsci/kfw248
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to DEHP induces premature reproductive senescence in male mice

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is the most commonly used phthalate, and it is an endocrine-disrupting chemical. This study tested a hypothesis that prenatal exposure to DEHP lays the foundation for premature gonadal dysfunction and subsequent reproductive senescence in male mice. Pregnant female CD-1 mice were orally dosed with vehicle control (tocopherol-stripped corn oil) or with 20 μg/kg/day, 200 μg/kg/day, 500 mg/kg/day, or 750 mg/kg/day of DEHP from gestational day 11 to birth. Overall, the prenatal D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 56 publications
9
67
2
2
Order By: Relevance
“…Additionally, levels of urinary phthalates and insecticides were also associated with lower sperm concentration, lower motility and increased percentage of sperm with abnormal morphology [72][73][74][75]. These results confirmed the results obtained by in vitro and in vivo studies [76,77].…”
Section: Effects Of Edcs On Sperm Production Morphology Motility Ansupporting
confidence: 86%
“…Additionally, levels of urinary phthalates and insecticides were also associated with lower sperm concentration, lower motility and increased percentage of sperm with abnormal morphology [72][73][74][75]. These results confirmed the results obtained by in vitro and in vivo studies [76,77].…”
Section: Effects Of Edcs On Sperm Production Morphology Motility Ansupporting
confidence: 86%
“…As a lack of exercise and a calorie-rich diet cannot fully explain the high occurrence of obesity and metabolic syndrome prevalent in the US population, we sought to examine ubiquitous environmental factors, specifically endocrine disruptors, for their ability to exacerbate weight gain and metabolic phenotypes. In particular, exposure to phthalates, a common chemical found in plasticizers, has been increasingly associated with obesity (Hurst and Waxman 2003, Snyder, Westerhoff et al 2003, Bility, Thompson et al 2004, Casals-Casas and Desvergne 2011, Janesick and Blumberg 2011, Heindel, Newbold et al 2015, Barakat, Lin et al 2017, Cardoso, Alves et al 2017), and recent studies suggest that phthalate exposure during the fetal period may increase this risk (Hatch, Nelson et al 2008). The underlying mechanism associated with the early effect of phthalate exposure on obesity has not been well established and is a topic of intensive investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of endocrine disruptors leads to metabolic deregulation, manifested by increased adipose deposition and disorder of glucose metabolism (Casals-Casas and Desvergne 2011, Heindel, Newbold et al 2015). However, much of the current knowledge about in utero and postnatal exposure to endocrine disruptors have been focused on development, particularly of reproductive systems (Barakat, Lin et al 2017, Cardoso, Alves et al 2017). The potential impact of interaction between endocrine disruptors and diet on global metabolic programming remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in fertility was earlier in rats exposed to high doses of DHEP (750 mg/Kg/day) and was associated with greater changes in the sex hormones and greater histological degeneration of the seminiferous tubules and the epididymis. Signs of germ cell apoptosis were also more evident in the treated group than in the controls, suggesting an association between prenatal exposure to DHEP and premature reproductive senescence induced by epigenetic changes in the pool of adult Leydig cell precursors [37]. More recently, the same authors reported that a mixture of phthalate esters similar to that found in the urine of pregnant American women caused, in the offspring of pregnant CD-1 mice, a reduction in testosterone and in the expression of mRNA of testicular steroidogenic genes (StAR, Cyp11, and Cyp17), and impaired spermatogenesis [38].…”
Section: Pre-natal Exposure: Can Testicular Function Already Be Comprmentioning
confidence: 92%
“…A more recent study by Barakat et al (2017) found a significant age-and dose-dependent reduction in the fertility of the offspring of pregnant rats administered DHEP compared to the controls. The decline in fertility was earlier in rats exposed to high doses of DHEP (750 mg/Kg/day) and was associated with greater changes in the sex hormones and greater histological degeneration of the seminiferous tubules and the epididymis.…”
Section: Pre-natal Exposure: Can Testicular Function Already Be Comprmentioning
confidence: 92%